(untitled) (American Journal of Research in Humanities and Social Sciences, 2025)
The concept of "political process" is used in political science to interpret and explain dynamic changes in the political life of society. The political process, as a universal category of political science, also characterizes political practice. It reflects the variability of politics and reveals the interaction of political institutions and political subjects performing certain functions and "roles." The political process can also be interpreted as the general activity of all subjects of political relations associated with the formation, development, change, and functioning of the political system, mediating state power.